2011
DOI: 10.1155/2011/953469
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic HPV Types Infection in Adolescents and University Women from North Portugal: From Self-Sampling to Cancer Prevention

Abstract: This study aimed to characterize the HPV infection status in adolescents and young university women in Portugal. The distribution of HPV genotypes was evaluated by PCR DNA genotyping after self-sampling collection from 435 women of exfoliated cervical cells using a commercial kit. We observed an overall frequency of HPV infection of 11.5%. Furthermore, HPV DNA prevalence was 16.6% in those young women that self-declared as sexually active. The more frequently detected HPV types were 31, 16, 53, and 61. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Several studies have shown that infection with high‐risk types of human papillomavirus (HPV) is a necessary but not sufficient cause of invasive squamous cell carcinoma of the cervix [zur Hausen et al, ; zur Hausen, ; Missaoui et al, ]. Other risk factors also increase the risk of cervical cancer, including sexually determinants, such as age at first sexual intercourse and number of sexual partners, tobacco and alcohol consumption, long‐term use of oral contraceptives, use of intrauterine device, multiple full‐term pregnancies, full‐term pregnancy at a young age, nutritional deficiencies, and co‐infection with other sexually transmitted infections (STIs), such as the human immunodeficiency virus, Chlamydia trachomatis , cytomegalovirus (CMV) within others [Matos et al, ; Broccolo et al, ; Missaoui et al, ; Chattopadhyay, ; Silva et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that infection with high‐risk types of human papillomavirus (HPV) is a necessary but not sufficient cause of invasive squamous cell carcinoma of the cervix [zur Hausen et al, ; zur Hausen, ; Missaoui et al, ]. Other risk factors also increase the risk of cervical cancer, including sexually determinants, such as age at first sexual intercourse and number of sexual partners, tobacco and alcohol consumption, long‐term use of oral contraceptives, use of intrauterine device, multiple full‐term pregnancies, full‐term pregnancy at a young age, nutritional deficiencies, and co‐infection with other sexually transmitted infections (STIs), such as the human immunodeficiency virus, Chlamydia trachomatis , cytomegalovirus (CMV) within others [Matos et al, ; Broccolo et al, ; Missaoui et al, ; Chattopadhyay, ; Silva et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Human papillomavirus (HPV) is a common sexually transmitted infection and has been shown in epidemiological and molecular studies to be a necessary etiologic agent for cervical cancer (Medeiros et al, 2005;Silva et al, 2011). In considering the factors responsible for the changes seen in HPV and cervical cancer epidemiology, viral factors (increased virulence and predominance of high-risk types), host factors (changes in behavior and immunity), and changes in screening and diagnosis were considered (Barnabas et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The examination of 435 fe male students conducted by Silva et al showed that 11% of HPV infections were caused mainly by type 31, 16, 53 and 61. The HPV infection percentage increased to 16% during sexual activity, and there was a correlation with the number of sexual partners and the period of sexual activity [2].…”
Section: Risk Factorsmentioning
confidence: 91%
“…As far as we know today, the main cause of cervical cancer is human papilloma virus (HPV) infection, in particular with high grade oncogenic HPV genotypes, such as HPV-16 and HPV-18, as well as co-occurrence of other factors predisposing women to cancer [1][2][3][4]. According to the WHO, the factors include smoking, multiple sexual partners, low socioeconomic status, herpes simplex virus (HSV) co-infection, human immunodeficiency virus (HIV) infection, and antioxidant and vitamin insufficiency in the diet.…”
Section: Introductionmentioning
confidence: 99%